Labile plasma iron levels predict survival in patients with lower-risk myelodysplastic syndromes - de Swart, Louise; Reiniers, Chloé; Bagguley, Timothy; van Marrewijk, Corine; Bowen, David; Hellström-Lindberg, Eva; Tatic, Aurelia; Symeonidis, Argiris; Huls, Gerwin; Cermak, Jaroslav; van de Loosdrecht, Arjan A; Garelius, Hege; et al. (Haematologica, 2018)
Red blood cell transfusions remain one of the cornerstones in supportive care of lower-risk patients with myelodysplastic syndromes. We hypothesized that patients develop oxidant-mediated tissue injury through the formation of toxic iron species, caused either by red blood cell transfusions or by ineffective erythropoiesis. We analyzed serum samples from 100 lower-risk patients with myelodysplastic syndromes at six-month intervals for transferrin saturation, hepcidin-25, growth differentiation factor 15, soluble transferrin receptor, non-transferrin bound iron and labile plasma iron in order to evaluate temporal changes in iron metabolism and the presence of potentially toxic iron species and their impact on survival. Hepcidin levels were low in 34 patients with ringed sideroblasts compared to 66 patients without. Increases of hepcidin and non-transferrin bound iron levels were visible early in follow-up of all transfusion-dependent patient groups. Hepcidin levels significantly decreased over time in transfusion-independent patients with ringed sideroblasts. Increased soluble transferrin receptor levels in transfusion-independent patients with ringed sideroblasts confirmed the presence of ineffective erythropoiesis and suppression of hepcidin production in these patients. Detectable labile plasma iron levels in combination with high transferrin saturation levels occurred almost exclusively in patients with ringed sideroblasts and all transfusion-dependent patient groups. Detectable labile plasma iron levels in transfusion-dependent patients without ringed sideroblasts were associated with decreased survival. In conclusion, toxic iron species occurred in all transfusion-dependent patients and in transfusion-independent patients with ringed sideroblasts. Labile plasma iron appeared to be a clinically relevant measure for potential iron toxicity and a prognostic factor for survival in transfusion-dependent patients. clinicaltrials.gov Identifier: 00600860.
Keywords: železo; Prognosis; senioři; lidé středního věku; proporcionální rizikové modely; Female; Humans; dospělí; přetížení železem; Aged; Male; ženské pohlaví; Blood Transfusion; Biomarkers; Middle Aged; prognóza; biologické markery; Iron; lidé; Myelodysplastic Syndromes; Erythropoietin; myelodysplastické syndromy; mužské pohlaví; erythropoetin; senioři nad 80 let; Iron Overload; Adult; krevní transfuze; Proportional Hazards Models; Aged, 80 and over